Kajian Antropologi Pariwisata dan Ethno-Ecotourism dalam Pengembangan Pariwisata di Provinsi Lampung - Bartoven Vivit Nurdin (Balitbangda Provinsi Lampung, 2016)
This paper aims to study the anthropology of tourism and build a model of ethno - ecotourism based on the potential of local knowledge for the development of local culture -based tourism in the province of Lampung. Tourism studies has been dominated by the perspective fields of physical science and economics, whereas failure of tourism management are there at the lack of socio-cultural studies that emphasize the human aspect in the development of tourism. This paper tries to analyze theoretically the relationship of culture, people and tourism in anthropology . Lampung has the abundant potential of natural resources for tourism development. All this time the strategy of tourism development rely solely on natural potentials and always featured physical potential , infrastructure and natural resources potential , but does not involve the human factor. The research method is an ethnographic approach. The results of this research showed that despite the potential of natural resources have a high sale tourism value, without being accompanied by a change in human behavior will not be succeed. Therefore, the model -based ethno - ecotourism local knowledge is highly relevant for the development of tourism in the province of Lampung , because all this time the development of tourism has not been done up. Tourism development policy must take a holistic approach , because human development is crucial progress of tourism. Besides, Lampung , have local knowledge potential in developing tourism.